Academic Stress and Nomophobia: Their Impact on Online Gaming Intensity on college students - Putri, Hadia; Yandri, Hengki; Harmalis, Harmalis (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2024)
Online gaming is a common problem among adolescents across various countries, often serving as an escape or distraction from academic stress and nomophobia. This study aimed to investigate the relationship between academic stress, nomophobia, and the intensity of online gaming among university students. Employing a quantitative descriptive correlational design, this research involved 304 students selected through convenience sampling. Data was collected using academic stress, nomophobia, and online gaming intensity scales and analyzed using IBM SPSS 25. The results revealed a significant correlation between academic stress and nomophobia with the intensity of online gaming (p < 0.05). Simultaneously, both independent variables explained 95.8% of the variance in online gaming intensity. These findings indicate that both academic stress and nomophobia contribute significantly to excessive online gaming behavior among university students. Consequently, this study recommends the implementation of guidance and counseling programs in higher education institutions to prevent and address online gaming addiction among students.